Internal company interaction on example of management accounting system in innovative project - E. V. Orlov; O. A. Smolyakov; E. O. Egorova (Управление)
In the context of the implementation of numerous innovative projects around the world, one of the urgent tasks of the modern theory of management accounting is the harmonisation of business processes within systems of various specialization (management, accounting, design and production) that form the organisational structure of the company and are at its various levels. The problem is the inconsistency of the activities of economic and design departments in the process of forming the concept of an innovative product, due to the lack of a model of the mechanism of their interaction at various stages of an innovative project. The article describes the initial stage of testing the hypothesis of the existence of an optimal model of management accounting and cost design systems (design department) interaction model at various stages of an innovation project. Within the framework of the study, a number of tasks were solved, in particular: the task of choosing the most effective research method from the list of methods used by the authors of similar scientific papers; the task of describing the mechanism of interaction of the considered intra-organisational systems in the context of the implementation of an innovative project; the task of establishing the identity of problematic issues arising from the interaction of the management accounting system and the design service at various enterprises. The purpose of the study is to test the hypothesis of the existence of an optimal model of management accounting and cost design systems interaction. Within the framework of the study with the participation of a representative group of three enterprises, the results characterising the current state of the management accounting and cost design systems were obtained. In practice, the enterprises under consideration face problems related to the management accounting and cost design systems interaction model, which are often accompanied by a low level of development of business processes and project management. As a result of the conducted research, indirect confirmation of the proposed hypothesis of the study was obtained.